Dietary diversity is associated with child nutritional status: evidence from 11 demographic and health surveys - Arimond, Mary; Ruel, Marie T. (Elsevier, 2004)
Simple indicators reflecting diet quality for young children are needed both for programs and in some research contexts. Measures of dietary diversity are relatively simple and were shown to be associated with nutrient adequacy and nutritional status. However, dietary diversity also tends to increase with income and wealth; thus, the association between dietary diversity and child nutrition may be confounded by socioeconomic factors. We used data from 11 recent Demographic and Health Surveys (DHS) to examine the association between dietary diversity and height-for-age Z-scores (HAZ) for children 6–23 mo old, while controlling for household wealth/welfare and several other potentially confounding factors. Bivariate associations between dietary diversity and HAZ were observed in 9 of the 11 countries. Dietary diversity remained significant as a main effect in 7 countries in multivariate models, and interacted significantly with other factors (e.g., child age, breast-feeding status, urban/rural location) in 3 of the 4 remaining countries. Thus, dietary diversity was significantly associated with HAZ, either as a main effect or in an interaction, in all but one of the countries analyzed. These findings suggest that there is an association between child dietary diversity and nutritional status that is independent of socioeconomic factors, and that dietary diversity may indeed reflect diet quality. Before dietary diversity can be recommended for widespread use as an indicator of diet quality, additional research is required to confirm and clarify relations between various dietary diversity indicators and nutrient intake, adequacy, and density, for children with differing dietary patterns. -- Authors' Abstract